Produkcia kyseliny mliecnej a ureázová aktivita u bachorových kmenov Enterococcus faecium a ich genetická stabilita - Lauková, A; Kuncová, M (Veterinarni medicina, 1991)
Lactic acid production, urease activity and genetic stability were investigated in five selected rumen strains of Enterococcus faecium. The average value of urease activity in the tested strains was 16.5 +/- 0.953 nkat per ml, two strains were urease-negative. The values of E. faecium strains produced lactic acid ranged from 1.087 +/- 0.134 to 1.787 +/- 0.213 mmol per 1 l. Cultivation of the strains in ethidium bromide (EB) eliminated urease activity of these strains already in the first subculture, but the elimination effects of sodium dodecyl sulphate (SDS) and acridine orange (AO) were manifested later on (1-8 subcultures). Lactic acid production was eliminated in all strains from 1st to 8th subculture after cultivation in SDS, EB and also AO.
Keywords: Lactic Acid; bachor; Sheep; Animals; ovce; Cattle; ureasa; Urease; Rumen; kyselina mléčná; Lactates; Enterococcus faecium; laktáty; zvířata; skot